Investigating students’ conceptual change in learning newton’s laws through a project-based learning design informed by understanding by design - Jovi Yuzzer Budiman; Achmad Samsudin; Ahmad Aminudin (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Misconceptions related to force and Newton’s Laws continue to be widely observed in secondary physics classrooms, often emerging from students’ everyday reasoning and instructional approaches that prioritize formula application over conceptual understanding. Aim: This study seeks to examine how a Project-Based Learning design informed by the Understanding by Design framework supports students’ conceptual change in learning Newton’s Laws. Method: The study employed a mixed-methods experimental design involving Grade XI high school students. Students’ conceptions were identified using a four-tier diagnostic test administered before and after instruction, complemented by questionnaires and semi-structured interviews. Quantitative analysis focused on conceptual change categories and N-change values, while qualitative data were used to explore students’ reasoning processes during learning activities. Results: The results show that students initially demonstrated a high prevalence of misconceptions, particularly in relation to Newton’s Third Law. Following the learning intervention, several students exhibited shifts toward scientifically accepted conceptions. Nevertheless, the overall magnitude of conceptual change remained low, indicating that while improvement occurred, it was not evenly distributed across students. Conclusion: The findings suggest that a PjBL approach guided by the UbD framework can facilitate conceptual change in learning Newton’s Laws, especially in addressing persistent misconceptions. However, the limited level of change highlights the need for more refined instructional designs, longer learning durations, and the integration of isomorphic diagnostic assessments to achieve stronger and more consistent conceptual development.